Seasonal Allergic Rhinitis: A focused systematic review and practice parameter update. Issue 4 (August 2017) - Wallace, Dana V.; Dykewicz, Mark S.
Abstract : Purpose of review: The review compares and contrasts seven major United States and international allergic rhinitis guidelines from 2008 to 2017. Recent findings: Despite many treatment options for allergic rhinitis, patients often report lack of therapeutic control and a reduced quality of life. Guidelines intended to improve allergic rhinitis care have been evolving into evidence based, systematic reviews, with less reliance on consensus of expert opinion characteristic of more traditional guidelines. The first Grading of Recommendations Assessment, Development, and Evaluation-based guideline developed in the United States for seasonal allergic rhinitis was first published in 2017. Summary: When critically analyzing the allergic rhinitis guidelines that use the rigorous Grading of Recommendations Assessment, Development, and Evaluation methodology, different groups of expert authors, using the same reference articles, will, at times, reach different conclusions regarding the quality of the evidence and the strength of the recommendation. Factors potentially contributing to these divergent determinations include: lack of objective primary outcome measures in allergic rhinitis, poorly defined Minimal Clinically Important Difference, failure to include all interested parties in guideline development, for example, patients, and subjectivity inherent in the expert panel.